2020
DOI: 10.1049/gtd2.12092
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the thermal analysis of power cables installed in polyvinyl chloride (PVC) ducts under continuous and cyclic current loading conditions

Abstract: A study of the performance of power cables installed inside non‐metallic ducts is presented here. Cable capacity calculations for this type of installation are done. The thermal analysis of cables inside ducts which are installed in air as riser or buried in soils is presented. According to IEC 60287 cables can be installed in fibre ducts in concrete layer surrounded by the soil, in this article it is proposed to install the cables in PVC ducts directly buried in the soil. Based on IEC 60287‐1‐3 and IEC 60853‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The diurnal and seasonal fluctuations in power demand and variable production from green energy plants create a cyclic thermal loading of the cable. The cyclic thermal loading of the cables is studied in both numerical [46] and theoretical [47] fashion. However, no experimental study is reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The diurnal and seasonal fluctuations in power demand and variable production from green energy plants create a cyclic thermal loading of the cable. The cyclic thermal loading of the cables is studied in both numerical [46] and theoretical [47] fashion. However, no experimental study is reported in the literature.…”
Section: Introductionmentioning
confidence: 99%